Design and Analysis of Microstrip Antenna - Abu Sharkh, Amani; Sweity, Tahreer; Salah, Yusra (جامعة بوليتكنك فلسطين - اتصالات, 2012)
The performance and advantages of microstrip patch antennas such as low weight, low profile, and low cost made them the perfect choice for communication systems engineers. They have the capability to integrate with microwave circuits and therefore they are very well suited for applications such as cell devices, WLAN applications, navigation systems and many others. In this project; a compact rectangular microstrip antenna performance with different types of feeding techniques are designed, for inset and edge feed at 2.4GHz compare the result that get from insert feed with edge feed design and analysis, and decide which design technique is the best, which obtain good bandwidth and return loss. Coaxial feed is designed to operate from 2 GHz to 12 GHz, and finally a proximity coupled microstrip antenna is designed to operate at 13GHz, and controlling the position of the feed line between the two substrates to optimize the return loss.
no of pages 108, 26445, اتصالات 16/2012 , in the store
Keywords: Microstrip Antenna